Bliska, a jednak obca: Skandynawia oczyma bohaterów prozy Natalii Tołstoj = So close and still far away: Scandinavia in the eyes of the protagonists of Natalya Tolstoy?s prose - Urban-Podolan, Aleksandra (1974- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article deals with the views of Russians and Scandinavians on each other - as found in short stories by Nataliya Tolstoy (1943-2010) in which she focuses on the differences in mentality, culture, and living standards between the two nations. The literary picture of Scandinavia and Russia shows a confrontation of the two realities: her protagonists view the North as an 'alien' land, yet a very desirable one - as a destination for travelers and migrants.
Keywords: Tołstoj, Natalia (pisarka rosyjska; 1943-2010); literatura rosyjska; opowiadanie rosyjskie; 20 w.